Arab Banker - Arab Bankers Association (London Arab Bankers Association, 2002)
The Arab Banker is aimed at financial sector professionals who either work for Middle East banks or conduct business with them. The editorial content includes features on banks and banking systems, interviews with senior bankers, and articles on broader financial markets that are relevant to Middle East finance (real estate finance, for example). The final pages of the magazine are devoted to cultural activities that are likely to be of interest to those involved with the Middle East.
Keywords: Banks and Banking; BANKING; FINANCE; FINANCIAL MARKET; MIDDLE EAST; PERIODICALS